Clinical and Electrophysiological Prognostic Factors of Childhood Absence Epilepsy - Hande Gazeteci Tekin; Pakize Karaoğlu; Pınar Edem (Journal of Pediatric Research, 2021)

(untitled)
Aim:Childhood absence epilepsy is common idiopathic epilepsy in childhood. This epilepsy, which has been shown to impair cognition, needs to be treated promptly and correctly. Therefore, determining its prognostic factors before treatment can provide prediction on the duration of treatment, drug selection, and drug dosage.Materials and Methods:The electroencephalography (EEG) and clinical findings of patients diagnosed with childhood absence epilepsy who were monitored for at least 12 months in the pediatric neurology clinics of two university hospitals between 2016 and 2020 were reviewed retrospectively. The patients were divided into two groups as responsive and unresponsive, according to seizures, EEG findings, and recurrent seizures after treatment. The epidemiological and clinical features of the two groups were compared.Results:Sixty-three patients who were diagnosed with childhood absence epilepsy according to the Panayiotopoulos criteria participated in this study. Thirty-nine (62%) of the patients were responsive to treatment (group 1), the remaining 24 patients (38%) (group 2) were unresponsive to treatment. Fifteen patients were valproate resistant, and nine patients relapsed after drug treatment withdrawal in group 2. The mean age of the patients was 7.87±1.68. The mean follow-up period was 29.1±13.6 (13-72 months) months. The mean age was lower in the responsive group of patients. The time between the onset of seizures and treatment was significantly longer in group 2. The number of patients with occipital intermittent rhythmic delta activity (OIRDA) in the responsive group was higher. A significant difference was found in the number of spike-slow wave complex and the amplitude of discharges between the two groups.Conclusion:In this study, it was seen that young age was an advantage for treatment response. Early initiation of treatment and OIRDA were good prognostic factors, while high amplitude and numerous discharges were among the poor prognostic factors.